Development of Interactive Learning Media Based on PowerPoint and Canva for Solar System Instruction at MTsN 5 Nganjuk: Pengembangan Media Pembelajaran Interaktif Berbasis PowerPoint melalui Aplikasi Canva pada Materi Bumi dan Sistem Tata Surya untuk Siswa Kelas VII MTsN 5 Nganjuk - Lailatul Badriyah; Mela Eka Nuri Cahyani (SEARCH: Science Education Research Journal, 2026)
This study is motivated by the need to provide more interactive science learning that actively engages students, particularly in the topic of the Solar System, which is abstract in nature and requires visualization. The purpose of this study is to develop interactive learning media based on PowerPoint using the Canva application for seventh-grade students at MTsN 5 Nganjuk. This research employs a Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects were 22 students from class VII-H. Data collection techniques included observation, interviews, expert validation, and student response questionnaires. The validation results indicate a feasibility percentage of 87.5% from material experts and 89.5% from media experts, both categorized as highly feasible. The small group trial yielded a percentage of 80%, while the large group trial resulted in 73.46%, both categorized as moderately attractive. Based on these findings, the interactive learning media based on PowerPoint through Canva is considered feasible and sufficiently engaging for use in science learning. This media can enhance student engagement and facilitate the understanding of abstract concepts through clearer visualization. Therefore, it has the potential to serve as an alternative technology-based learning medium for teaching the Solar System in schools.